2010
DOI: 10.1111/j.1944-9720.2010.01063.x
|View full text |Cite|
|
Sign up to set email alerts
|

From the Virtual World to the Real World: A Model of Pragmatics Instruction for Study Abroad

Abstract: With its focus on the use of language forms in cultural context, the study of pragmatics can be a valuable component in a program that prepares students to learn both language and culture in study abroad. The goal of the present study is to propose a model for pragmatic instruction in study abroad that fosters both intercultural competence and language skills, is informed by research and practice, and takes advantage of the affordances that an immersion environment and new technologies offer. The article provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(53 citation statements)
references
References 44 publications
3
47
0
3
Order By: Relevance
“…If pragmatic competence is one of the goals of the SA experience, the students should be made aware of the pragmatic norms of the host culture before and during the course of their time abroad. SA programs should develop this knowledge through explicit instruction, awareness-raising activities, communicative output practice, targeted feedback, and guided reflection (e.g., Hernández, 2018;Hernández & Boero, 2018;Kondo, 2010;Martínez-Flor & Usó-Juan, 2006;Shively, 2010). The model I envision is based on second language acquisition constructs (e.g., noticing, pushed output) that are thought to facilitate language development.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If pragmatic competence is one of the goals of the SA experience, the students should be made aware of the pragmatic norms of the host culture before and during the course of their time abroad. SA programs should develop this knowledge through explicit instruction, awareness-raising activities, communicative output practice, targeted feedback, and guided reflection (e.g., Hernández, 2018;Hernández & Boero, 2018;Kondo, 2010;Martínez-Flor & Usó-Juan, 2006;Shively, 2010). The model I envision is based on second language acquisition constructs (e.g., noticing, pushed output) that are thought to facilitate language development.…”
Section: Resultsmentioning
confidence: 99%
“…Second language (L2) pragmatic development has received increasing attention in study abroad (SA) research (e.g., Bataller, 2010;Henery, 2015;Hernández, 2016;Shively, 2010Shively, , 2016Shively & Cohen, 2008). A large body of this research suggests that L2 learners tend to become more target-like after a semester or more abroad (e.g., Churchill & DuFon, 2006;DuFon, 2010;Kasper & Rose, 2002;Shively, 2010Shively, , 2016Shively & Cohen, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 (2) 12 (2) 24 (4) 24 (4) 6 (1) Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 2/7/15 1:55 AM A higher percentage of learners in the highest interaction group reported interacting with NS friends (65%), service personnel (77%), NS with whom they play sports (24%), and NS with whom they worship (24%). Learners with more contact also report interacting with more different types of speakers: Learners in the 1-3 and 4 -6 intensity bands reported interaction with NS in two different conversational roles (a mean of 2.24 and 2.23, respectively) whereas learners in the highest intensity group reported contact with NS in three different roles (a mean of 2.94 speakers).…”
Section: A Post-hoc Analysis Of Interactionmentioning
confidence: 95%
“…Rodriguez (2001) found that study-abroad and at-home learners showed similar development in recognition of request strategies in L2 Spanish over a semester. 1 Not all features change in the same amount of time: In the semester that it took for L2 speakers to adjust the speech acts they performed and increase mitigation toward targetlike use in advising sessions, they did not reduce their use of aggravators which were found neither in the input during the sessions nor the turns of native-speaking classmates (Bardovi-Harlig and Hartford 1993). After four months abroad, learners' accuracy of comprehension of indirect refusals scored consistently better than indirect opinions (Taguchi 2008).…”
Section: Length Of Staymentioning
confidence: 97%